1997
DOI: 10.1099/0022-1317-78-8-1829
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic, non-infectious polio subviral particles synthesized in Saccharomyces cerevisiae.

Abstract: Polioviral genes coding for P1, the precursor for the structural proteins, and 3CD, the viral protease, were cloned in a Saccharomyces cerevisiae inducible expression system. N-antigenic empty capsids could be isolated from the yeast cell extract provided that pirodavir, a capsid-binding compound and capsid stabilizer, was added during the induction period and during purification. Purification was by immunoaffinity chromatography. The purified empty capsids had the same immunogenicity as poliovirus virions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Immunogenic, but unstable, VLPs were also produced by recombinant expression in yeast [16]. A strategy to address this instability is described here where candidate stabilising mutations were identified then multiple changes introduced into capsid proteins in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Immunogenic, but unstable, VLPs were also produced by recombinant expression in yeast [16]. A strategy to address this instability is described here where candidate stabilising mutations were identified then multiple changes introduced into capsid proteins in combination.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first time that this has been reported for SVDV, although it has been done for other enteroviruses, by use of baculovirus recombinants in insect cells (6,21,39), vaccinia recombinants in mammalian cells (2), and the yeast Saccharomyces cerevisiae (35). Recombinant VLPs have been produced on the basis of the expression of full-length polyprotein (39), the P1 and 3CD proteins (21,35), the P1 and P3 proteins (2), or the individual VP0, VP3, and VP1 proteins (6) in several expression systems. The yield (20 to 180 g/liter) of VLP obtained by single recombinant (based on the expression of full-length polyprotein) (39) was enhanced compared to that obtained by multiple baculovirus recombinants (6, 21) but was still not satisfactory for development of a subunit vaccine or diagnostic antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies demonstrated the production of empty capsids of several picornaviruses following translation of the viral RNA in rabbit reticulocyte lysates (25,30,45) or expression of capsid precursor in bacterial (34), yeast (55), insect (14) and mammalian (1,3) cells. In these studies, capsid precursors were coexpressed with the viral protease in order for capsid assembly to occur within the expression system.…”
mentioning
confidence: 99%